Characterization of alveolar epithelial cells type II during postnatal lung development in relation to alveolarization – Stereological studies of rat lungs - Julia Hüttmann; Lars Knudsen; Andreas Schmiedl (PLoS ONE, 2025)
Objective Rats are born with morphologically immature lungs, but intact surfactant system. The aim of this study was to characterize the surfactant producing alveolar epithelial cells type II (AEII) during alveolarization and find relationships between the intracellular surfactant pool and alveolar surface area, lung volume and body weight. Methods After exsanguination, lungs of 3, 7, 14, 21 and 90 days old rats were inflated with a pressure of 10 mm H 2 0 and fixed by perfusion and prepared for light and electron microscopy. Using different stereological parameters AEII were characterized. Results At day 21, the end of bulk alveolarization, the alveolar surface and the number of AEII increased significantly but their volume and size did not change compared to values before alveolarization. The number of AEII, but not the AEII volume correlated significantly with alveolar surface and lung volume. The size and volume weighted mean volume of lamellar bodies (Lb) as well as the Lb volume per AEII did not change during alveolarization. Total Lb volume was significantly higher at the end of bulk alveolarization compared to values before alveolarization. Conclusion The adaptation of the intracellular surfactant during postnatal development occurred predominantly by increasing the number of AEII.